Heterogeneity in Torajan Ritual Speech: Metalinguistic Awareness and the Nationâs Character Building - Sandarupa, Stanislaus; Assagaf, R.S.M.; Hasyim, Husain (SOSIOHUMANIKA, 2015)
ABSTRACT: The research is aimed at studying heterogeneity in Torajan ritual speech through the process of entextualization. The research shows that in the event of speaking by a single speaker, there occurs the process of the decontextualized text segments from other genres of prose narrative, such as historical narratives, myths, legends, and poetic argumentation, which is then recontextualized in the present performance. The method used is participant observation. The field notes are analyzed from domain, taxonomic, componential, and thematic analysis. The techniques used are recording, videotaping, and field notes. The research has two findings: ethnographic and academic. Ethnographically, it is found that the Torajan ritual speech spoken by a single speaker, the âtominaâ, is actually heterogeneous. Theoretically, it shows that homogeneity in language is tenable only if evaluation is based on grammar. However, this research is able to show the heterogeneity in Torajan ritual speech. The sources of the texts are ârettengâ, poetic argumentation, and the myth of âTulang Didiâ. The values of the three forms of life, such as human beings, animals, and plants, are found. From this appear, the harmonious relations between human and God, human and human, human and animals, and human and plants. These values may contribute to the nationâs character building.KEY WORD: Heterogeneity, metalinguistic awareness, entextualization, ritual speech, nationâs character building, and Toraja people.Â RESUME: âHeterogenitas dalam Tuturan Ritual Toraja: Kesadaran Metabahasa dan Pembangunan Karakter Bangsaâ. Penelitian ini bertujuan untuk mempelajari heterogenitas dalam tuturan ritual di Toraja lewat proses entekstualisasi. Hasil penelitian menunjukkan bahwa dalam peristiwa tutur yang dilakukan oleh seorang penutur terjadi proses dekontekstualisasi segmen teks dari jenis-jenis narasi prosa, seperti narasi historis, mitos, legenda, dan argumentasi puitik yang direkontekstualisasikan ke dalam performansi sekarang. Metode yang dipakai adalah observasi partisipan. Hasil catatan lapangan dianalisis dari sudut domain, taksonomik, komponensial, dan tematis. Teknik penelitian yang dipakai adalah rekaman, video, dan catatan lapangan. Ada dua hasil penelitian: etnografi dan akademik. Secara etnografis, tuturan ritual Toraja yang dituturkan oleh satu orang, âtominaâ, sebenarnya heterogen. Secara teoretis, diketengahkan bahwa homogenitas dalam bahasa hanya bisa dipertahankan kalau dilihat dari sudut tata bahasa. Namun, penelitian memperlihatkan heterogenitas dalam tuturan ritual Toraja. Sumber-sumber teks adalah ârettengâ, argumen puitik, dan ceritera Tulang Didi. Ditemukan nilai-nilai tiga pucuk kehidupan, seperti manusia, hewan, dan tanaman. Nilai-nilai ini memperlihatkan relasi antara manusia dengan Yang Kuasa, manusia dan manusia, manusia dan hewan, serta manusia dengan tanaman. Nilai-nilai ini dapat dipakai untuk memperkokoh pembangunan karakter bangsa.KATA KUNCI: Heterogenitas, kesadaran metabahasa, entekstualisasi, tuturan ritual, pembangunan karakter bangsa, dan bangsa Toraja.Â Â Â Â About the Authors: Stanislaus Sandarupa, R.S.M. Assagaf & Husain Hasyim are Lecturers at the Faculty of Humanities UNHAS (Hasanuddin University) Makassar, Jalan Perintis Kemerdekaan Km.10, Makassar City, South Sulawesi, Indonesia. Corresponding author is: torindo@indosat.net.idHow to cite this article? Sandarupa, Stanislaus, R.S.M. Assagaf & Husain Hasyim. (2015). âHeterogeneity in Torajan Ritual Speech: Metalinguistic Awareness and the Nationâs Character Buildingâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(1) Mei, pp.29-38. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (April 28, 2015); Revised (May 20, 2015); and Published (May 30, 2015).